New wine in an old bottle? A facet-level perspective on the added value of Grit over BFI–2 Conscientiousness - Schmidt, Fabian T. C.; Lechner, Clemens M.; Danner, Daniel (PLOS ONE, 2020)
There is emerging consensus that Grit’s two facets—perseverance of effort and consistency of interest—are best understood as facets of the Big Five dimension of Conscientiousness. However, an in-depth investigation on whether Grit’s facet offer any added value over more established facets of Conscientiousness is absent from the literature. In the present study, we investigated whether Grit’s facets are empirically distinguishable from three facets of Conscientiousness as conceived in the well-validated Big-Five Inventory 2 (BFI–2), namely, Organization, Responsibility, Productiveness. Moreover, we investigated whether Grit’s facets show different (and possibly stronger) associations than the facets of Conscientiousness with a broad set of external criteria (age, educational attainment, monthly income, life satisfaction, mental and physical health, fluid and crystallized intelligence); as well as whether the criterion correlations of Grit’s facets are incremental over Conscientiousness. Findings from two latent-variable models in a large and diverse sample (N = 1,244) indicated that the facets of Grit showed moderate to strong relationships related to each other and to the three Conscientiousness facets of the BFI–2 (.41 ≤ r ≤ .94). Grit–Perseverance was almost indistinguishable from the Productiveness facet of Conscientiousness, whereas Grit–Consistency appeared to capture something unique beyond the Conscientiousness facets. The relationships with external criteria of Grit’s facets were similar in direction and size to those of the Conscientiousness facets. The results give further purchase to the view that Grit’s facets can be subsumed under the Conscientiousness domain.